STRUCTURAL AND MAGNETIC PROPERTIES OF FE/SI MULTILAYER GROWN BY HELICON PLASMA SPUTTERING - Setyo Purwanto; Isao Sakamoto; M. Koike; H. Tanoue (Jurnal Sains Materi Indonesia, 2003)
STRUCTURAL AND MAGNETIC PROPERTIES OF FE/SI MULTILAYER GROWN BY HELICON PLASMA SPUTTERING. Helicon plasma sputtering method has been used to grown the Fe/Si multilayer (MLs) with various thickness of Silicon spacer around 0.5 ~ 2nm for Fe thickness ﬁxed at 2nm in order to investigated the antiferromagnetic coupling behaviour. Also we grown the MLs with various Fe thickness around 2-5nm for Silicon spacer fixed at tSi =l nm and l.5nm. Present study found that in case of Silicon spacer thickness tSi= l nm multilayer ﬁlm exhibit antiferromagnetically ordering, beside this thickness the MLs are ferromagnetic. The maximum magnetoresistance ratio is 0.22%, it appears at the Fe thickness tFe=3nm and Si thickness tSi=l nm.